(untitled) (Research, Society and Development, 2020)
Objective: to analyze the nursing care for the prevention and control of scabies that are being performed according to research published in the last 10 years (2009-2019). Methodology: an integrative literature review was performed in June 2019, considering articles indexed in the Scientific Electronic Library Online (Scielo) databases; Nursing Database (BDENF); Medical Literature Analysis and Retrieval System Online (Medline); and Virtual Health Library Database (VHL), Cumulative Index to Nursing and Allied Health Literature (Cinahl), Scopus e Cochrane Collaboration. Results: of the 54 articles found, 4 met the inclusion criteria, all in English, which evidenced the lack of research on the subject. Conclusion: the results showed that the nursing interventions performed involve adequate cleaning of patients’ clothes, bedding and equipment that may have been contaminated, as well as isolation of patients, however, it was found that the guidelines are heterogeneous, varying between teams of health.